Inwestycje produkcyjne o znaczeniu ponadregionalnym w planistycznych dokumentach krajowych i wojewódzkich = The production investments of supraregional importance in national and voivodship documents of planning - Skiba, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Article refers to the impact assessment of spatial policy on the location of productive investment, and proposals were formulated on the basis of planning documents Lubuskie province. The study reveals policy documents and planning at the regional, region and country level. Spatial planning is presented as a system of regulations and decisions affecting the formation of productive investment.
Keywords: planowanie przestrzenne; polityka regionalna; polityka sektorowa; spatial planning; regional policy; sectoral policy